1993
DOI: 10.1002/ana.410340604
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of medial temporal lobe epilepsy: I. Results of history and physical examination

Abstract: In order to more precisely define a syndrome of medial temporal lobe epilepsy, histories and physical findings were evaluated in 67 patients studied with intracranial electrodes who had medial temporal seizure onset and became seizure free following temporal lobectomy. Patients with circumscribed, potentially epileptogenic mass lesions were excluded. Fifty-four patients (81%) had histories of convulsions during early childhood or infancy, 52 of which were associated with fever. Complicated febrile seizures occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
507
3
33

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 786 publications
(581 citation statements)
references
References 28 publications
24
507
3
33
Order By: Relevance
“…Second, removal of the affected hippocampus eliminates seizures in 80 -90% of TLE patients exhibiting unilateral mesial temporal lobe sclerosis (Falconer et al, 1964;Ojemann, 1987). Third, stereotypic neuropathology is found in the hippocampus of TLE patients that is recapitulated in animal models of TLE, termed hippocampal sclerosis (Schwartzkroin and Knowles, 1984;Sutula et al, 1988;Houser et al, 1990;French et al, 1993;Mello et al, 1993;Buckmaster and Dudek, 1997). Given that the hippocampus is critical in TLE, are there specific hippocampal circuits which could play a dominant role in the regulation of excitability, and could damaged function in these areas be particularly significant in the epileptic brain?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, removal of the affected hippocampus eliminates seizures in 80 -90% of TLE patients exhibiting unilateral mesial temporal lobe sclerosis (Falconer et al, 1964;Ojemann, 1987). Third, stereotypic neuropathology is found in the hippocampus of TLE patients that is recapitulated in animal models of TLE, termed hippocampal sclerosis (Schwartzkroin and Knowles, 1984;Sutula et al, 1988;Houser et al, 1990;French et al, 1993;Mello et al, 1993;Buckmaster and Dudek, 1997). Given that the hippocampus is critical in TLE, are there specific hippocampal circuits which could play a dominant role in the regulation of excitability, and could damaged function in these areas be particularly significant in the epileptic brain?…”
Section: Introductionmentioning
confidence: 99%
“…To address these issues, we used voltage-sensitive dye (VSD) imaging and combined whole-cell dendritic patch recordings to determine changes in circuitry in the pilocarpine rat model of epilepsy. This animal model shares a natural history of develop-ment with human TLE in that it is characterized by a latent or silent period between the pilocarpine-induced initial injury and the onset of recurrent seizures, as well as shared neuropathology (French et al, 1993;Spencer and Spencer, 1994). High-speed voltage-sensitive dye imaging offers sufficient spatial and temporal resolution to record simultaneously membrane potential changes in 6400 voltage sensors at high sampling frequency (1-2 kHz) Salzberg et al, 1973;Contreras and Llinás, 2001;Ang et al, 2005), which enables coincident recording of afferent, intrinsic and efferent responses after synaptic activation in multiple hippocampal circuits.…”
Section: Introductionmentioning
confidence: 99%
“…Three decades ago, Goodridge and Shorvon noted an intermittent pattern of AED response in which refractory seizures are interrupted by periods of remissions of at least two years in 12% of their patients 2 . Also, French et al reported in a surgical series of adult patients with MTLE that a quarter had experienced previous periods of remission 6 . In our study, we observed higher rates of relapse-remitting pattern in both MTLE-HS and MTLE-NL.…”
Section: Discussionmentioning
confidence: 98%
“…The natural history of MTLE-HS has been extensively studied 6,7 . However, the natural history of MTLE with different underlying causes, especially MTLE in patients with normal MRI, is still not fully understood.…”
mentioning
confidence: 99%
“…A frequent hallmark in the histories of patients with temporal lobe epilepsy (TLE), particularly if associated with hippocampal sclerosis (mesial TLE), is the occurrence of prolonged febrile seizures (FS) early in life [21,38,44,72], prompting suggestions that the FS are a causal factor in the etiology of this epileptic disorder [6,52]. However, most FS (affecting 2-14% of all children worldwide; [46,71 for review]) do not lead to epilepsy, and certain risk factors have been distinguished.…”
Section: Febrile Seizures and Epileptogenesismentioning
confidence: 99%